Cheerful Discontent: Understanding the Well-being Paradox in Sub-Saharan Africa - Talita Greyling; Stephanie Rossouw; Martijn J. Burger (Global Labor Organization (GLO), 2025)
Positive affect and life evaluation are positively correlated in Sub-Saharan Africa (SSA), but the relationship is much weaker than in Western countries, revealing a disconnect between how people feel and how they judge their lives. Using Gallup World Poll microdata (2013-2024) for 39 SSA and 27 Western countries, we construct a metric that measures the difference in positive affect and life evaluation scores (named PA-LE balance) and apply eXtreme Gradient Boosting (XGBoost) with SHapley Additive exPlanations (SHAP) to uncover its drivers. Our results show that the PA-LE balance for SSA has a wider distribution, and more than two-thirds of individuals are classified as "cheerfully discontented" (positive balance). In contrast, Western countries have a narrower distribution with approximately the same number of individuals classified as "cheerfully discontented" and "contentedly despairing" (negative balance). Uncovering the drivers of these observed differences in the PA-LE balance reveals that the most important predictors are the same across SSA and Western countries; two subjective factors, individual optimism and negative affect, account for roughly two-thirds of the variation in the balance. Further analyses show that low economic optimism, combined with low negative affect, is characteristic of the African scenario, meaning people feel happier than their life evaluations suggest. This suggests that, amid low levels of optimism due to resource constraints and low expectations, especially regarding youth prospects, strong social ties and satisfaction with one's place buffer against daily worry, sadness, or stress and sustain higher positive affect, creating a situation of cheerful discontent.
Keywords: I31; O55; C55; Z13; 330; Life evaluation; positive affect; Africa; XGBoost; SHAP